Substance Abuse Disorders : Evidence and Experience. - Ghodse, Hamid (John Wiley & Sons, 2011)
Substance abuse disorders are among the most prevalent psychiatric disorders and are frequently comorbid with other psychiatric and health conditions and accompanied by social problems; however, they remain under-recognized and under-treated. Many physicians and mental health practitioners receive little-to-no training in the identification and treatment of these disorders. Approaches to their prevention include some of the major success stories in modern public health as well as some of the deepest controversies in public life. This new title in the WPA series Evidence and Experience in Psyc.